Pertanggungjawaban Pidana Pelaku Pemberian Izin Ekspor Benih Lobster (Studi Putusan Pengadilan Negeri Jakarta Pusat Nomor 26/Pid.Sus-TPK/2021/PN Jkt.Pst) - Ibrahim, Bisma Harun; Sudja’i, Sudja’i; Handayani, Budi (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2024)
This research examines the criminal liability of perpetrators granting lobster seed export permits, with a focus on the corruption case involving the former Minister of Maritime Affairs and Fisheries, Edhy Prabowo. The aim of the research is to analyze forms of abuse of authority and criminal liability that can be imposed on perpetrators. The research method used is normative juridical with a statutory and case approach. The results of the research show that Edhy Prabowo's actions were proven to violate Article 12 letter a of the Corruption Eradication Law jo. Article 55 paragraph (1) 1st jo. Article 65 paragraph (1) of the Criminal Code. The abuse of authority took the form of issuing permits to export lobster seeds unlawfully for personal and certain group interests. The criminal liability imposed includes imprisonment for 5 years, a fine of IDR 400 million subsidiary to 6 months in prison, revocation of political rights for 3 years after serving the principal sentence, and payment of compensation of IDR 9.6 billion and 77,000. There are aggravating reasons because corruption was carried out while serving as a public official and during the Covid-19 pandemic. This case shows the importance of strengthening the supervisory system in granting export permits as well as strict law enforcement to provide a deterrent effect. This research recommends increasing understanding of regulations for state officials and implementing appropriate punishments for perpetrators of corruption to ensure the sustainability of domestic fisheries and the Indonesian fisheries ecosystem.